2010
DOI: 10.1063/1.3428674
|View full text |Cite
|
Sign up to set email alerts
|

Multistate electron transfer dynamics in the condensed phase: Exact calculations from the reduced hierarchy equations of motion approach

Abstract: Multiple displaced oscillators coupled to an Ohmic heat bath are used to describe electron transfer (ET) in a dissipative environment. By performing a canonical transformation, the model is reduced to a multilevel system coupled to a heat bath with the Brownian spectral distribution. A reduced hierarchy equations of motion approach is introduced for numerically rigorous simulation of the dynamics of the three-level system with various oscillator configurations, for different nonadiabatic coupling strengths and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
109
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 85 publications
(164 reference statements)
0
109
0
Order By: Relevance
“…We shall show that over the broad regimes considered, the RC model captures all important system-environment correlations for EET in the presence of both underdamped and overdamped environments, agreeing perfectly with numerically exact data generated using the HEOM. [42][43][44][45] Furthermore, we demonstrate that the RC model significantly outperforms the closely related Zusman equations, 70,73,77 a set of drift-diffusion equations often used to describe tunnelling processes in molecular systems, which we derive from the RCME in a semiclassical limit. We also examine the role that a structured environment may play in the dimer energy transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We shall show that over the broad regimes considered, the RC model captures all important system-environment correlations for EET in the presence of both underdamped and overdamped environments, agreeing perfectly with numerically exact data generated using the HEOM. [42][43][44][45] Furthermore, we demonstrate that the RC model significantly outperforms the closely related Zusman equations, 70,73,77 a set of drift-diffusion equations often used to describe tunnelling processes in molecular systems, which we derive from the RCME in a semiclassical limit. We also examine the role that a structured environment may play in the dimer energy transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…25,37,39,40 A multitude of powerful computational methods have been developed to deal with the difficulties faced in modelling strongly dissipative quantum systems. Examples include the hierarchical equations of motion (HEOM), [41][42][43][44][45][46] density matrix renormalisation group (and related) techniques, 25,36,47,48 and those based on the path integral formalism. [49][50][51][52] All can converge to numerically exact results in specific circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…63,64 The present approach can also be applied to a system driven by pulses of arbitrary number, shape, and strength, as well as a system with time-dependent ET couplings. 62 The present formulation can also be extended to multimode Brownian oscillator systems by introducing a higher dimensional hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82][83] While most research with the HEOM approach assumed the Drude spectral distribution, we have shown that the ET problem can be handled in a nonperturbative manner for both the system-bath and ET couplings by applying the hierarchy formalism to the Brownian oscillator (BO) spectral distribution that arises from the canonical transformation of ET system. [62][63][64] Because realistic environments in many cases involve both the overdamped Drude and underdamped Brownian modes as shown by molecular dynamics simulations, [84][85][86][87][88] an extension to the multimode case is necessary. In this paper, we demonstrate a way to deal with the Drude+BO spectral distribution in the framework of HEOM formalism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation